2014
DOI: 10.1038/jcbfm.2014.119
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal NAMPT is Released after Cerebral Ischemia and Protects against White Matter Injury

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) has been implicated in neuroprotection against ischemic brain injury, but the mechanism underlying its protective effect remains largely unknown. To further examine the protective effect of NAMPT against ischemic stroke and its potential mechanism of action, we generated a novel neuron-specific NAMPT transgenic mouse line. Transgenic mice and wild-type littermates were subjected to transient occlusion of the middle cerebral artery (MCAO) for 60 minutes. Neuron-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…Regional cerebral blood flow was reduced similarly by 93.5 % and 92.4 % in AQP4 +/+ and AQP4 −/− mice during occlusion, and was restored at 15 min after reperfusion to 44.9 % and 47.1 % of baseline values before occlusion. These results are typical of reported MCAO studies in mice [9, 29]. …”
Section: Resultssupporting
confidence: 90%
“…Regional cerebral blood flow was reduced similarly by 93.5 % and 92.4 % in AQP4 +/+ and AQP4 −/− mice during occlusion, and was restored at 15 min after reperfusion to 44.9 % and 47.1 % of baseline values before occlusion. These results are typical of reported MCAO studies in mice [9, 29]. …”
Section: Resultssupporting
confidence: 90%
“…Similar observations were made in a mouse model [18,83]. Both eNAMPT and iNAMPT protein expression was detectable with two different NAMPT antibodies in WT C57BL/6 mice.…”
Section: Roles Of Nampt In Brain Ischemiasupporting
confidence: 83%
“…We then provided evidence that the protective effects are mediated by eNAMPT. Conditioned medium from NAMPT-overexpressing neurons exposed to OGD protected cultured oligodendrocytes from OGD and these effects were abolished with neutralizing antibodies [18]. Thus, we concluded that NAMPT may not function simply in a restricted intracellular manner during stroke recovery but that it protects both gray matter and WM from stroke injury through extracellular actions.…”
Section: Roles Of Nampt In Brain Ischemiamentioning
confidence: 95%
“…89 Whether eNAMPT exhibits pro-inflammatory or antiinflammatory activity is still the subject of debate. 21,[58][59][60]90,91 However, several studies have reported pro-inflammatory effects of eNAMPT on different cell types, which include induction of inducible nitric oxide synthase, 92 activation of extracellular signal-regulated protein kinase 1/2 (ERK1/2), 66 nuclear factor NF-κB activation 92,93 and production of cytokines such as TNF-α, IL-6, IL-1β, 93,94 transforming growth factor β 95 and monocyte chemoattractant protein 1. 96 Production of inflammatory cytokines and NAMPT expression in adipocytes, thus, seem to be regulated by a positive feedback activation loop.…”
Section: Pathophysiological Role Of Namptmentioning
confidence: 99%